2021
DOI: 10.21203/rs.3.rs-251903/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Feasibility of Combining Brain Radiation and Fingolimod in Healthy Rodents and in Humans With Newly Diagnosed Glioblastoma

Abstract: PURPOSE: Severe and long-lasting lymphopenia occurs in 40% of patients with malignant gliomas and is associated with inferior survival. Inadvertent irradiation of circulating lymphocytes is a major contributor to this lymphopenia. Fingolimod causes striking but reversible lymphopenia by sequestering circulating lymphocytes in lymphoid tissues. Fingolimod could potentially reduce iatrogenic immunosuppression by decreasing the number of lymphocytes in circulation during radiation. However, combining radiation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Fingolimod and Fingolimod phosphate have a low renal clearance associated with a drug half-life of around 6–9 days and thus display stable concentrations in the bloodstream [ 81 ]. Nevertheless, only one not-yet-peer-reviewed clinical study has been carried out in the GBM context, but no data on efficacy were evaluated [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fingolimod and Fingolimod phosphate have a low renal clearance associated with a drug half-life of around 6–9 days and thus display stable concentrations in the bloodstream [ 81 ]. Nevertheless, only one not-yet-peer-reviewed clinical study has been carried out in the GBM context, but no data on efficacy were evaluated [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most frequent drug used in this context is FTY720 (fingolimod) from Novartis that was initially used as a drug for the treatment of multiple sclerosis. Grossman et al examined the feasibility of combining Fingolimod to the standard-of-care for newly diagnosed GBM patients in a single arm trial [ 170 ]. The results of this trial highlighted important safety concerns with this combination, including prolonged lymphopenia [ 170 ].…”
Section: Clinical Trials Using Activators or Inhibitors Of Pp2amentioning
confidence: 99%
“…Grossman et al examined the feasibility of combining Fingolimod to the standard-of-care for newly diagnosed GBM patients in a single arm trial [ 170 ]. The results of this trial highlighted important safety concerns with this combination, including prolonged lymphopenia [ 170 ]. It is reported that FTY720 can indirectly activate PP2A by blocking SET binding [ 171 ].…”
Section: Clinical Trials Using Activators or Inhibitors Of Pp2amentioning
confidence: 99%